The Charismatic Leader : Quaid-i-Azam Mohammad Ali Jinnah and the Creation of Pakistan - Sikandar Hayat (Karachi Oxford University Press, 2015)
Hayat tells the story of Quaid-i-Azam Mohammad Ali Jinnah, who emerged as the leader of the Muslims in British India between 1937-47. They faced a distressful situation as India advanced towards freedom. Jinnah came to their rescue, showed them a way out in a separate homeland of Pakistan, and led them in their struggle for freedom and independence.
Include Bibliography and Index.
It is a biography.
Keywords: Pakistan movement -- Politics and government -- Jinnah, Mahomed Ali, 1876-1948 -- Statesmen -- Pakistan -- India